A predictive model of impurity diffusion coefficients in face-centered-cubic metallic systems based on machine-learning. (March 2021) - Wei, Zhen Bang; Wang, Cui Ping; Xu, Wei Wei; Han, Jia Jia; Lu, Yong; Liu, Xing Jun
Abstract: This paper develops models for diffusion coefficient prediction to provide parameters for atomic mobility databases and to assist material design in a multi-scale simulation framework for face-centered-cubic (fcc) alloys. Models of impurity-diffusion activation energy ( Q I ) and self-diffusion activation energy ( Q s ) are trained using machine-learning with experimental diffusion data and basic physical properties. The values of Q s in body-centered cubic (bcc), fcc and hexagonal close-packed (hcp) can be well-predicted using melting temperature, electronic configuration, atomic properties and elasticity parameters. Estimates of Q I in fcc metallic systems calculated using a model with six features agreed well with experimental data. Compared with previous models of Q s and Q I, the newly developed models exhibit higher coefficients of determination ( R 2 ) and significantly lower mean absolute errors. The self- and impurity-diffusion coefficients in fcc metallic systems can be simulated by these models. The models are also successfully applied during the assessment process of the Ni–Ti binary atomic mobility database. Thus, the developed models provide an easy and reliable method for estimating the self- or impurity-diffusion coefficients of fcc alloys when they are unavailable. Graphical abstract: Image 1 Highlights: The models for self- and impurity diffusion in the FCC alloys were developed by machine-learning methods. No matter the phase is stable or not, the diffusion coefficients the FCC alloys were well predicted. The developed models were applied to predict diffusion coefficients in fcc Ni–Ti binary system successfully.